Análise histológica, parasitológica e morfométrica da pele de orelha de cães naturalmente e experimentalmente infectados com leishmania (leishmania) chagasi - Maria Marta Figueredo (2009)
Although 90% of clinical cases of American visceral leishmaniasis (AVL) occur in the northeastern region of Brazil, the incidence of cases in recent years has increased in southeastern states such as Minas Gerais (MG), where the disease has been reported in several cities including Belo Horizonte, the state capital. Some studies have shown a strong correlation between the incidence of AVL and canine visceral leishmaniasis (CVL) in Belo Horizonte. A study of 108 dogs with parasite Leishmania chagasi detected by immunohistochemistry in healthy ear skin was obtained from 2 distinct geographical areas: 55 from ametropolitan area of the municipality (Santa Luzia, MG) and 53 dogs from a central area of Belo Horizonte. In parallel, a group of 10 beagles were experimentally infected with L. chagasi. Considering the clinical aspects of all naturally infected dogs, symptomatic dogs were more frequent than asymptomatic ones, especially, animals from the metropolitan area compared with the central area (79.6% and 20.3%, respectively). A chronic exudate was observed in the ear of 51 out of 55 dogs naturally infected from the metropolitan area (92.7%) and 45 out of 53 dogs naturally infected from the central area (84.9%). However there is a weak positive correlation between the parasite load and the chronic inflammatory reaction because we found cases where the presence of Leishmania was not directly incriminated in the presence of an inflammatory reaction. Importantly, asymptomatic dogs from the central area harbor more parasites in the skin than the asymptomatic ones from metropolitan area. In addition, a profound difference was noted in the intensity of the inflammatory reaction and parasite load in the skin ofexperimental infected dogs.